2014
DOI: 10.1200/jop.2014.001488
|View full text |Cite
|
Sign up to set email alerts
|

Changing Physician Incentives for Affordable, Quality Cancer Care: Results of an Episode Payment Model

Abstract: Modifying the current fee-for-service payment system for cancer therapy with feedback data and financial incentives that reward outcomes and cost efficiency resulted in a significant total cost reduction. Eliminating existing financial chemotherapy drug incentives paradoxically increased the use of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 4 publications
1
93
0
Order By: Relevance
“…Alternative payment models may provide the needed stimulus for this kind of care redesign [18][19][20], as current fee-for-service payment systems provide little incentive for institutions to make systematic investments in outpatient acute care [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Alternative payment models may provide the needed stimulus for this kind of care redesign [18][19][20], as current fee-for-service payment systems provide little incentive for institutions to make systematic investments in outpatient acute care [21].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As an example, in a recent value-based pilot, identification of high inpatient use and comparison to peers resulted in implementation of a strategy to prevent readmissions with reported success. 8 A major strength of this study is that we measured patterns of care at the practice level, a suitable organization unit for interventions, particularly alternative payment models. This is an important extension of the literature demonstrating variation across geographical regions, as geographical units are not well suited to payment policies because decision making generally occurs at the practitioner or organizational level.…”
Section: Exhibitmentioning
confidence: 99%
“…5,6 Cost savings have been reported in several pilot studies testing the use of clinical decision support and bundled payment models to incentivize the use of cost-effective treatments when equally efficacious regimens exist. 7,8 Other research has demonstrated variation in the use of inpatient services for patients with advanced cancer at the regional level but not doi: 10 at the practice level. 9 Some pilot projects have reported reductions in inpatient utilization through enhanced care management.…”
mentioning
confidence: 99%
“…The model succeeded in achieving a 10-percent reduction in readmissions, shortening the average length of stay, and reducing hospital charges (Casale et al, 2007) and subsequently led Geisinger to develop bundled payment for elective coronary angioplasty, bariatric surgery, perinatal care, and treatment of some chronic conditions. United Healthcare ran a bundled payment pilot for oncology care between 2009 and 2012 that involved five sites and reportedly achieved a 34-percent cost savings without a negative impact on quality (Newcomer et al, 2014).…”
Section: Bundled and Performance-based Payment Approachesmentioning
confidence: 99%